Challenges to the implementation of the performance management system in the Mofumahadi Manapo Mopeli Regional Hospital - Ntsutle, Diphoko Samuel (My University, 2012)
Introduction Performance management system is set of techniques used to plan, direct and improve the performance of employee in line with organizational objectives. Performance management is a critical management responsibility to ensure achievement of the organization strategic goal. The performance management system is a good initiative in the public sector but faces critical implementation challenges. The implementation of performance management system in Mofumahadi Manapo Mopeli Regional Hospital is regarded as a challenge because of the increase number of complaints and disputes at the end of the cycle. Main Aim To identify the challenges in the implementation of the performance management system at Mofumahadi Manapo Mopeli Regional Hospital. Methodology The study is a descriptive cross sectional study and based on a self administered questionnaires to the personnel working in Mofumahadi Manapo Mopeli Regional Hospital. Data was collected over a period of one month and an assistant was used to distribute and collect the data. The assistant followed up with all unit managers v to increase the return of questionnaires. The data collected was kept confidential and anonymous. The data processing was done by the researcher and the information from the questionnaire was analysed in Excel program. Research limitation: There was a low return of questionnaires due to the lack of interest in participation in research as participation is voluntary. Changes in the personnel statistics such as resignation and transfers of officials during the financial year affected the population size during the period of the data collection. Result: Overall the study found that employees do not like the system because of inconsistency. The supervisors are not held accountable for the monitoring of PDMS and conduct inadequate evaluations and apply inconsistent processes. The implementation process is left up to the supervisors and the employees and often takes place at the last minute of the performance cycle. Organisational value and short term rewards overlook high performers.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the Degree of Master of Public Health
Keywords: Personnel Management